Large value payment systems and the role of regulation - Manning, Mark (Henry Stewart Talks, 2010)
Historical origins of payment systems and link to central bank objectives and policy interest, Sources of risk in large-value payment systems and how system design has evolved to mitigate these risks, The case for public intervention in payment systems, Different forms of public intervention